Effect of thiourea on growth, yield and quality of vegetable cowpea (Vigna unguiculata L. Walp) (Indian Journal of Arid Horticulture, 2020)
The field experiment was conducted on "Effect of thiourea on growth, yield and quality of vegetable cowpea (Vigna unguiculata L. Walp)" at Horticulture farm, Department of Horticulture, S.K.N. College of Agriculture, Jobner (Rajasthan) during kharif, 2018. The experiment consisting six levels of thiourea (control, seed treatment with 500 ppm thiourea, seed treatment with 1000 ppm thiourea, foliar application of 500 ppm thiourea, foliar application of 1000 ppm thiourea and seed treatment with 500 ppm thiourea + foliar application of 500 ppm thiourea) in randomized block design with three replications. Results indicated that application of seed treatment with thiourea 500 ppm and foliar application of thiourea 500 ppm significantly increased the plant height (64.15 cm), branches per plant, chlorophyll content, pods per plant (24.85), pod length, pod yield per per ha (148.67 q), nitrogen, phoshporus, protein content and crude fiber content in green pod over control and other treatments. The seed treatment with thiourea 500 ppm with foliar application of thiourea 500 ppm found significantly superior with net returns (Rs. 212675/ha) and highest B:C ratio (3.51).
Keywords: Growth; quality; thiourea; vegetable cowpea; yield